Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Composition and structure of natural mixed-oak stands in northern and central Portugal - Carvalho, João P. F. (Forest Ecology and Management, 2011)
Stand composition and structure of natural mixed-oak stands of common-oak (Quercus robur L.) and pyrenean-oak (Quercus pyrenaica Willd.) were studied. Diverse compositional and structural elements in early and late successional stand stages were analysed. The study was conducted in north and central Portugal where different naturalmixed oak forests types are located. The followingmixed-oak forest types involving common-oak and pyrenean-oak were studied: common-oak & other hardwoods; commonoak & cork-oak (Quercus suber L.); ash (Fraxinus angustifolia Vahl) & pyrenean-oak; and pyrenean-oak & madrone (Arbutus unedo L.). Measurements were made in early and late successional stand stages on the different mixed oak forest types. Different stand characteristics and indices were used to describe and compare stand structure and composition. The study showed changes in species diversity and stand structure. Most tree species in mature stands are present in early stages but with higher abundance. Shannon diversity index may change between 0.798 and 1.915. Signiﬁcant differences on species diversity and abundance were found depending on the forest type and successional stage. Mature mixed-oak forests have high species diversity with an abundance of small to medium tree size species. Species distribution and diameter differentiation indices range from 0.30 to 0.70 and 0.52 to 0.82, respectively, revealing signiﬁcant structural complexity. The average number of standing and downed dead trees was 265 and 83 trees ha−1 for early and late stage, respectively, with 6.9 and 65.4 m3 ha−1 . Higher values of stand diversity index were 41 and 53 in more complex and developed forests. Later stand stages have complex structure, with a wider range of tree diameter distribution and higher degree of irregularity.
Keywords: Quercus pyrenaica Willd.; Quercus robur L.; Stand composition; Stand Structure

Analisi strutturale e caratterizzazione della necromassa in sugherete della Calabria - Barreca, L.; Marziliano, P. A.; Menguzzato, G.; Scuderi, A. (iForest - Biogeosciences and Forestry, 2010)
The cork forests are one the most interesting forest ecosystems in the Mediterranean area. Their distribution and ecological characteristics have undergone a significant transformation after the significant changes following the development and establishment of agricultural crops. Currently, only a few stands, which survive in hard to reach places, prove the wide spread distribution of this species was also in the recent past. This study describes the stand structure of some cork forests in Calabria region (southern Italy). In order, to characterize the vertical structure Latham index has been applied, while for the description of the horizontal distribution NBSI group indices has been used. Detailed surveys on dead wood were also conducted determining the occurring volume and its decay stage according to the decay classes system proposed by Hunter. The aim of this study is to provide guidelines for sustainable management of cork forests, improving and promoting the structural complexity and functional efficiency of these forest stands.
The following values have no corresponding Zotero field: pub-location: Dipartimento Gestione dei Sistemi Agrari e Forestali (GESAF), Universit degli studi Mediterranea di Reggio Calabria, Localit Feo di Vito, I-89060 Reggio Calabria (Italia) publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Dead Wood; Quercus Suber L; Stand Structure; Structural Index; Sustainable Forest Management

Drought-Induced Multifactor Decline of Scots Pine in the Pyrenees and Potential Vegetation Change by the Expansion of Co-occurring Oak Species - Galiano, L.; Martínez-Vilalta, J.; Lloret, F. (Ecosystems, 2010)
Episodes of drought-induced tree dieback have been recently observed in many forest areas of the world, particularly at the dry edge of species distributions. Under climate change, those effects could signal potential vegetation shifts occurring over large geographical areas, with major impacts on ecosystem form and function. In this article, we studied the effect of a single drought episode, which occurred in summer 2005, on a Scots pine population in central Pyrenees (NE Spain). Our main objective was to study the environmental correlates of forest decline and vegetation change at the plot level. General and generalized linear models were used to study the relationship between canopy defoliation, mortality and recruitment, and plot characteristics. A droughtdriven multifactor dieback was observed in the study forest. Defoliation and mortality were associated with the local level of drought stress estimated at each plot. In addition, stand structure, soil properties, and mistletoe infection were also associated with the observed pattern of defoliation, presumably acting as long-term predisposing factors. Recruitment of Scots pine was low in all plots. In contrast, we observed abundant recruitment of other tree species, mostlyQuercus ilexand Q. humilis, particularly in plots where Scots pine showed high defoliation and mortality. These results suggest that an altitudinal upwards migration of Quercusspecies, mediated by the dieback of the currently dominant species, may take place in the studied slopes. Many rear-edge populations of Scots pine sheltered in the mountain environments of the Iberian Peninsula could be at risk under future climate scenarios.
Keywords: canopy defoliation; Drought; mistletoe; mortality; pinus sylvestris l; Recruitment; scots pine; scots pine (Pinus sylvestris L.); soil properties; Stand Structure; summer; summer water availability; Water availability